If x + y = 6, then solve for y to get: y = 6 - x.
Now replace y with 6 - x in both equations.
(5x)/3 + 6 - x = c
2(6 - x) = c - 4x
The upper equation is solved for c.
Now we solve the lower equation for c.
c = 2(6 - x) + 4x
c = 12 - 2x + 4x
c = 2x + 12
Since we have two equations solved for c, we substitute to get
(5x)/3 + 6 - x = 2x + 12
This is an equation in only x, so we can solve for x.
(5x)/3 - 3x = 6
5x - 9x = 18
-4x = 18
x = -9/2
Now we solve for y.
x + y = 6
-9/2 + y = 6
y = 9/2 + 12/2
y = 21/2
Now we solve for c.
c = (5x)/3 + y
c = (5 * (-9/2))/3 + 21/2
c = -45/6 + 21/2
c = -15/2 + 21/2
c = 6/2
c = 3
Answer: c = 3
No, the expressions –0.5(3x 5) and –1.5x 2.5 are not equivalent.
Using the distributive property to expand the first expression, you would get -1.5x - 2.5. Since the constant term does not have the same sign as the second expression, the two expressions are not equivalent.
Also, if you substitute in a value for x and evaluate each expression, the values will not be equal.
Learn more about Equivalent:
brainly.com/question/26992243
#SPJ4
Answer:
2.22
Step-by-step explanation:
Answer:
A
Step-by-step explanation:
(because -4 is equal to -4 and meets the condition of the top inequality, you plug in -4 into the top function)
Answer:
$179.76
Step-by-step explanation:
We can calculate the total cost as follows. The 1.00 represents the before-tax cost of the dehumidifier and the 0.0575 the 5.75% sales tax:
Total cost of dehumidifier = (1.00+0.0575)($169.99) = $179.76 (to the nearest
cent()